Parasit Gastrointestinal pada Hewan Ternak di Tempat Pemotongan Hewan Kabupaten Sigi, Sulawesi Tengah - Intan Tolistiawaty; Junus Widjaja; Leonardo Taruk Lobo; Rina Isnawati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Disease in lifestock due to gastrointestinal parasites can cause economic loss and harmful for health of breeders or people who eat meat from these animals. . Slaughterhouse is an important place for monitoring parasitism in livestock, surveillance of disease in livestock and zoonoosis. Previous studies showed that some people living nearby a swine slaughterhouse were infected with Ascaris lumbricoides and Trichuris trichura. Based on those results, it is required to study about the gastrointestinal parasites in livestock which could transmit to human in Slaughterhouse in Jono Oge Village and Biromaru Slaughterhouse, Sigi regency. This study was a cross-sectional design, and fecal samples collection were carried out on 97 cattles, 33 pigs and 33 goats slaughtered at slaughterhouse of Sigi, Central Sulawesi. Samples from cattleswere examined according to sedimentation method, while those from pigs and goats were examined using Ritchie method. Single infections by Facsiola sp., Paramphistomum sp., Trichuris sp., Oesophagustomum sp., Ascaris sp., Eimeria sp., and Balantidium sp. were found in cattle and pigs. In cattle, dual infections were found which caused by Strongyloidea sp. and Paramphistomum sp., Trichuris sp. and Paramphistomum sp., Fasciola sp. and Paramphistomum sp. A mixed infection also observed in cattles which caused by Paramphistomum sp., Fasciola sp., and Trichuris sp. while Trichostrongylus sp., was found in goat